2021
DOI: 10.3390/ijerph18052237
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Association between Atrial Fibrillation and 90-Day Adverse Outcomes among Older Adults with Heart Failure: A Retrospective Cohort Study

Abstract: Sex differences in the prognostic impact of coexisting atrial fibrillation (AF) in older patients with heart failure (HF) have not been well-studied. This study, therefore, compared sex differences in the association between AF and its 90-day adverse outcomes (hospital readmissions and emergency room (ER) visits) among older adults with HF. Of the 250 older adult patients, the prevalence rates of coexisting AF between male and female HF patients were 46.0% and 31.0%, respectively. In both male and female older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Studies have shown that in China, the prevalence of heart failure in adults is 1.5%. Especially, the incidence of the elderly people over 70 years old is even more than 11% [1]. Statistics reveal that among more than 1,200 patients with heart failure or atrial fibrillation, 3% have both atrial fibrillation and heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that in China, the prevalence of heart failure in adults is 1.5%. Especially, the incidence of the elderly people over 70 years old is even more than 11% [1]. Statistics reveal that among more than 1,200 patients with heart failure or atrial fibrillation, 3% have both atrial fibrillation and heart failure.…”
Section: Introductionmentioning
confidence: 99%